Detecting the correlation between mobile learning behavior and personal characteristics among elementary school students. Issue 8 (17th November 2018) - Sun, Zhong; Yao, Xiajing; You, Jiaxin; Du, Wenli; Luo, Liming
ABSTRACT: This study aimed to explore the features of mobile learning behaviors among Chinese elementary school students, and relationships between mobile learning behaviors and personal characteristics in mobile learning environment. The current study designed and developed a game-based educational mobile environment and conducted an experimental research. Eighty-three elementary students participated in this study. The results revealed the features of elementary school students' mobile learning behavior including: 1) the students had reasonable login frequencies and learning time duration with appropriate guidance from the teachers, and satisfying learning performance by self-learning; 2) higher grade, learning style with active information processing and higher test scores in the conventional Chinese subject course had positive impacts on the mobile learning behaviors, but no gender difference was found. Regrettably, students showed more digital consuming than digital creating in the current study. The results could provide necessary suggestions on mobile learning for young learners.